Jod-Basedow phenomenon: Phenomenal thyrotoxicosis? - Ozturk, Tuncer; Sengul, Demet; Sengul, Ilker (Sanamed, 2021)
A Deucalione iodine is an essential mineral vital for the optimal function of the thyroid gland in human beings. Apart from being found in a variety of foods, it is a component of various medications, amiodarone and expectorants, iodine-based swabs used for skin cleaning before interventional and surgical procedures, and iodinated contrast media in medical settings. Jod-Basedow Phenomenon, also known as Jod-Basedow Syndrome or iodine-induced thyrotoxicosis, is a rare cause of thyrotoxicosis that characteristically refers to a paradoxical phenomenon in which large loads of exogenous iodine can cause hyperthyroidism. This phenomenon is mainly seen in populations already at risk for thyroid diseases, such as autoimmune thyroid diseases, prior thyroid surgical history, latent Graves' disease, and prior non-toxic diffuse or nodular goiter formation, or those with underlying kidney disease, such as chronic kidney disease and end-stage renal disorders, which can impact iodine excretion. Typically, it is recognized in those with the administration of a large iodine load, dietary supplement, iodinated contrast media used in conjunction with computed tomography scans, angiography, and various other imaging studies, iodinated antiseptic solutions and oral supplements, or a medication, mainly amiodarone, class III antiarrhythmic drug used in the treatment of recurrent severe ventricular arrhythmias, paroxysmal atrial tachycardia, atrial fibrillation and maintenance of sinus rhythm after cardioversion of atrial fibrillation. Prophylactic medical management of the phenomenon may include antithyroid drugs, methimazole, or perchlorate, to be considered for patients at risk for developing iodine-induced thyrotoxicosis that is scheduled for imaging modalities by using iodinated contrast media. Moreover, the preliminary management modality comprises cessation of iodine administration, avoiding further exposure, administration of beta-adrenergic antagonists, thionamides, corticosteroids, and rarely lithium. Prognosis is usually favorable, although a small percentage of cases could suffer permanent sequelae from iodine-induced thyrotoxicosis. Nevertheless, complications are remarkable including thyroid storm, permanent hyperthyroidism, atrial fibrillation, and fetal hypothyroidism with goiter development, in terms of ordering iodinated contrast media in pregnants. Jod-Basedow Phenomenon should not be overlooked and should be managed by an interprofessional healthcare team serving and officiating not only to treat it but also to concern themselves, actively in the relevant prophylaxis.